2023
DOI: 10.1051/0004-6361/202346221
|View full text |Cite
|
Sign up to set email alerts
|

Emission line variability of young 10–30 MJup companions

D. Demars,
M. Bonnefoy,
C. Dougados
et al.

Abstract: Context. Emission lines that are indicative of active accretion have been observed for a number of low-mass companions (M < 30 MJup) to stars. Line variability is ubiquitous on stellar accretors, but it has never been characterized in detail for low-mass companions. Such characterizations can offer insights into the accretion mechanism at play. Aims. We aim to characterize the short-to-long-term H I Paschen β emission line variability of two 10 to 30 MJup companions on wide orbits: GQ Lup b and GSC 06214-00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 150 publications
3
13
0
Order By: Relevance
“…Along with the asymmetric line profiles nicely fit with multiple velocity shifts and widths, these features are consistent with the magnetospheric accretion models. A <1% filling factor has also been inferred for the two 10-30 M Jup wide companions GQ Lup B and GSC 06214-00210 B (Demars et al 2023).…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Along with the asymmetric line profiles nicely fit with multiple velocity shifts and widths, these features are consistent with the magnetospheric accretion models. A <1% filling factor has also been inferred for the two 10-30 M Jup wide companions GQ Lup B and GSC 06214-00210 B (Demars et al 2023).…”
Section: Discussionmentioning
confidence: 69%
“…Nonetheless, accretion variability has been found to increase on longer timescales for young stars (e.g., Nguyen et al 2009;Mendigutía et al 2011;Pogodin et al 2012;Costigan et al 2014;Zsidi et al 2022), brown dwarfs (e.g., Stelzer et al 2007), and even for substellar companions (Demars et al 2023). Stelzer et al (2007) found that accretion onto the 20-30 M Jup brown dwarf 2MASS J12073346-3932539 mildly varied between 10 −7.1 and 10 −6.8 M Jup yr −1 (a factor of two) for two consecutive nights, but changed by at least a factor of 10 on monthly to yearly timescales.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations